Effect of oil palm shell powder on the mechanical performance and thermal stability of polyester composites - Nabinejad, O.; Debnath, Sujan; Rahman, Muhammad; Davies, Ian (Elsevier, 2015)
This paper presents an experimental study on the development of polymer bio-composites. The composites were fabricated from unsaturated isophethalic polyester resin containing powdered oil palm shell (OPS) as a function of powder particle size. The influence of washing OPS powder in methanol to remove surface impurities was also investigated with the tensile and flexural strengths and moduli improving significantly (between 22.9% and 61.4%) for the composites containing washed OPS powder compared to the unwashed case. It was observed that the composite tensile and flexural strength generally increased with decreasing powder size with the strength of the composite containing 75–150 μm OPS powder being similar to that of the pure matrix. However, the tensile and flexural moduli of the composites were found to be essentially independent of powder size. Thermogravimetric analysis (TGA) in flowing oxygen indicated that the addition of OPS powder shifted the thermal degradation peak of the bio-composite from 370 °C to 418 °C.